The Inclusion of Next Generation Science Standards (NGSS) and Bloom’s Taxonomy in the Science and Life Textbook for Fifth Grade in Palestine - Zyoud, Osama; Khataybeh, Abdalla; Rababaa , Ebtisam (Dirasat: Educational Sciences, 2021)
This study aims at detecting the degree to which the science and life textbook for fifth grade in Palestine included the next generation of science standards (NGSS) and Bloom’s taxonomy levels. The study used a content analysis card designed according to NGSS. The tool’s reliability and validity were confirmed. The study adopted a descriptive analytical method. The results showed that the field of disciplinary core ideas came first, with a remarkably high percentage of (68.4%), while the field of crosscutting concepts came next, with a low percentage of (16.7%). The field of science and engineering practices ranked third, with a low percentage of (14.9%). They also demonstrated that there is a marked disparity when applying the levels of Bloom’s taxonomy through which the next generation of science standards (NGSS) appeared. More accurately, the lower level of cognitive skills (remembering and understanding) hit a high percentage of (90.3%), compared to the higher-level cognitive skills (applying, analyzing, creating, and evaluating) which came low with a percentage of (9.7%).